EFFECT OF FEE BASED INCOME AND OPERATIONAL COSTS ON PROFIT IN PT. SHARIA INDONESIAN PEOPLE'S BANK - karlina karlina; ikhwanuddin harahap; Windari windari; ali ali (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This research is motivated by decline in profitability in the first quarter of 2017 which is thought to be influenced by income, especially income derived from services (fee based income) and operating cost. The purpose of this study was to determine the effect of fee based income and operating cost on profits at PT. Bank Rakyat Indonesia Syariah both partially and simultaneously. This study is a quantitative study, data analysis techniques with multiple linear regression analysis, with data processing used through the SPSS 23 Program. The results of the study show that simultaneously fee based income and operating costs affect earnings. But partially, fee based income variables hasn’t effect on earnings. While operating costs affect earning. The coefficient of determination (R2) obtained R2 of 0,552. This show that 55,2% of each profit growth can be explained by the variable fee based income and operating costs, the remaining 44,8% is explained by other variables outside this study.